Factors Influencing Nurse Compliance with Personal Protective Equipment - Intan Diana Putri; Yuniati Yuniati (Hasanuddin Medan, 2022)
Nurses have a high risk of exposure to disease thus occupational safety and health must be prioritized. Many nurses continue to disregard the usage of personal protective equipment. The purpose of this study was to investigate the characteristics that influence nurse compliance with the usage of personal protective equipment. This was a cross-sectional survey done at Langsa City Regional Hospital. The total population of nurses was 472 persons, and the sample size was 100. Data was analysed using univariate and bivariate analysis, as well as the chi-square test and multiple logistic regression at a 95% confidence level (a=0.05). The findings revealed that attitudes (p=0.001), PPE availability (p=0.001), skills (p=0.008), and supervision (p=0.004) impacted nurses' compliance with the usage of PPE at the hospital. Knowledge (p=0,226) and information (p=0,239) were variables that had no effect. The variable that has the greatest influence on nurses' adherence to the usage of PPE is the changeable availability of PPE. Nurses reported that if complete personal protective equipment was available, the likelihood of being obedient to wear PPE was six times greater than responders who stated that PPE was only partially available. The conclusion shows that nurses' compliance with the use of PPE is affected by the availability of PPE, attitudes, supervision, and skills. It is suggested to the management of Langsa City Regional Hospital to provide more complete personal protective equipment as needed in every action and further improves supervision of nurses in complying using personal protective equipment.